2010
DOI: 10.1111/j.1365-2184.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage differentiation of dental follicle cells and the roles of Runx2 over‐expression in enhancing osteoblast/cementoblast‐related gene expression in dental follicle cells

Abstract: Multipotent DFCs can be induced to differentiate towards osteoblasts, adipocytes or chondrocytes in vitro. Runx2 over-expression up-regulated expression levels of osteoblast/cementoblast-related genes and in vitro enhanced osteogenic differentiation of DFCs. In addition, mutant Runx2-induced changes in DFCs were more prominent than those induced by full-length Runx2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 52 publications
(62 reference statements)
5
46
0
Order By: Relevance
“…Vascular smooth muscle cell (VSMC) can lose the expression of smooth muscle lineage markers and begin to express osteogenic markers and deposit a mineralized bone-like matrix [14][15][16][17][18][19]. During the mineralization of VSMC, runt-related transcription factor2 (Runx2), a transcription factor expressed at early stages of osteoblast differentiation, is upregulation [20], and in concert with osterix by regulating the expression of osteoblast-related gene [21], such as osteopontin (OPN) contributes to VC [22]. Recent study suggested that klotho knockdown can accelerate VSMC calcification through a Runx2-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular smooth muscle cell (VSMC) can lose the expression of smooth muscle lineage markers and begin to express osteogenic markers and deposit a mineralized bone-like matrix [14][15][16][17][18][19]. During the mineralization of VSMC, runt-related transcription factor2 (Runx2), a transcription factor expressed at early stages of osteoblast differentiation, is upregulation [20], and in concert with osterix by regulating the expression of osteoblast-related gene [21], such as osteopontin (OPN) contributes to VC [22]. Recent study suggested that klotho knockdown can accelerate VSMC calcification through a Runx2-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Runx2 (Cbfa1) is a key transcription factor essential for skeletal and tooth development, acting at very early stages to drive the expression of mineralization proteins, like DSPP, BSP, ALP, OCN etc. [42,43]. Remarkably, low expression of Runx2 has been previously observed in differentiating odontoblasts, unlike the high expression in other mineralizing tissues; suggesting the odontoblastic lineage diverges from the osteoblastic [44].…”
Section: Xxxe15mentioning
confidence: 86%
“…We noticed that the terms, DFSCs (dental follicle stem cells) and DFC/DFCs (dental follicle cells) have been used in the literature to denote the DF derived cells that are capable of differentiation. For example, in the publications by Pan et al and Guo et al [21, 22], the DFCs were established by culturing the DF derived cells in α-MEM +FBS, which was the same medium used in our study to establish the DFSCs. We use DFSCs to reflect the facts that the cell population possesses the stem cell properties of multi-lineage differentiation.…”
Section: Discussionmentioning
confidence: 99%